Evaluation of Rapid stool antigen test for the diagnosis of Helicobacter pylori infection in patients with dyspepsia (IMC Journal of Medical Science, 2017)
Background and objectives: Several diagnostic assays are used for the detection of Helicobacter pylori infection in suspected peptic ulcer cases. H. pylori stool antigen test is a non-invasive method for the detection of active infection. The present study has evaluated the efficacy of rapid stool antigen test to diagnose H. pylori infection in patients with dyspepsia.Materials and methods: Adult patients with complains of dyspepsia attending the Department of Gastroenterology, Hepatobiliary and Pancreatic Diseases (GHPD) of BIRDEM hospital for endoscopy were included. Gastric biopsy, blood and stool samples were obtained from each participant after informed written consent. Rapid urease test (RUT), serum H. pylori immunoglobulin A (IgA) and IgG and rapid H. pylori stool antigen (HpSAg) tests were performed. Only stool samples were obtained from 31 neonates aged 1 to 30 days as negative control for HpSAg test.Results: A total of 91 adult patients with complain of dyspepsia were included in the study. Out of 91 cases, 17 (18.7%) and 74 (81.3%) had peptic ulcer and erosion respectively. HpSAg was positive in 63.7% cases compared to 42.9% and 62.6% respectively by RUT and IgA. The rate of HpSAg positivity was significantly higher (p